2015
DOI: 10.1210/jc.2015-1732
|View full text |Cite
|
Sign up to set email alerts
|

SerumN1-Methylnicotinamide Is Associated With Obesity and Diabetes in Chinese

Abstract: Context:Nicotinamide N-methyltransferase (NNMT) is a novel histone methylation modulator that regulates energy metabolism, and NNMT knockdown prevents diet-induced obesity in mice. However, whether NNMT plays a role in human obesity and type 2 diabetes (T2DM) remains to be elucidated.Objective: NNMT catalyzes methylation of nicotinamide to generate N 1 -methylnicotinamide (me-NAM). We aimed to investigate the associations of serum me-NAM with obesity and T2DM in Chinese.Design, Setting, and Participants: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 27 publications
7
60
1
Order By: Relevance
“…No association between NNMT expression and BMI was found in this study, as has been suggested by rodent data [38]. In contrast, Liu and colleagues reported a positive correlation between circulating MNAM and BMI, waist and hip circumference (BMI r = 0.22, p < 0.001 in men; r = 0.13, p = 0004 in women) in a larger cohort of 1160 Chinese individuals [19]. Curiously, the average BMI in the study by Kaant and colleagues was in between 33 and 47 for control and T2D individuals, respectively.…”
Section: Nnmt and Methyl Donor Balancesupporting
confidence: 52%
See 2 more Smart Citations
“…No association between NNMT expression and BMI was found in this study, as has been suggested by rodent data [38]. In contrast, Liu and colleagues reported a positive correlation between circulating MNAM and BMI, waist and hip circumference (BMI r = 0.22, p < 0.001 in men; r = 0.13, p = 0004 in women) in a larger cohort of 1160 Chinese individuals [19]. Curiously, the average BMI in the study by Kaant and colleagues was in between 33 and 47 for control and T2D individuals, respectively.…”
Section: Nnmt and Methyl Donor Balancesupporting
confidence: 52%
“…Human adipose tissue NNMT expression correlates positively with adiposity and insulin resistance [18,19]. Consistent with these correlations, antisense NNMT knockdown (NNMT ASO) in vivo protected C57BL6 mice from fat accumulation on a high fat diet (HFD) and improved their glucose tolerance compared with controls [38].…”
Section: Nnmt and Methyl Donor Balancementioning
confidence: 92%
See 1 more Smart Citation
“…[4][5][6] Our recent epidemiological study also revealed that serum me-NAM, an indicator of NNMT activity, was associated with obesity and diabetes mellitus in a Chinese population. 7 Because obesity and diabetes mellitus were independent risk factors for the development of CAD, 8,9 we hypothesized that increased serum me-NAM levels might be associated with CAD. Indeed, upregulation of hepatic NNMT activity and subsequent increase in plasma me-NAM levels were associated with the progression of atherosclerosis in an animal model.…”
mentioning
confidence: 99%
“…Kraus et al [7] reported that NNMT expression is increased in white adipose tissue (WAT) and liver of obese and diabetic mice, and NNMT knockdown in WAT and liver protects against diet-induced obesity by increasing cellular energy expenditure. Liu et al [8] found that serum MNA was associated with obesity and diabetes. Hong et al [9] showed that nicotinamide N-methyltransferase regulated hepatic nutrient metabolism.…”
Section: Introductionmentioning
confidence: 99%